Rapid determination of the immobilization conditions for lead and cadmium in soil using 2, 4, 6-trimercaptotriazine, trisodium salt, nonahydrate - Jiang, Ke; Zhou, Kanggen; Zhang, Jiangsheng (Journal of Environmental Engineering and Landscape Management, 2019)
Chemical immobilization is widely used for remediation of heavy metal contaminated soils. The present study proposed a method for the immobilization of lead (Pb) and cadmium (Cd) in soil using 2, 4, 6-trimercaptotriazine, trisodium salt, nonahydrate (TMT). Simulation tests were performed in an aqueous solution to rapidly screen the operational conditions. The effects of TMT dosage, reaction pH, and the coordination ions (Al3+, Fe3+) on immobilization, and the thermodynamics for the TMT-DTPA-Zn-Pb-H2O system, were investigated. The results showed that the immobilization efficiencies of Pb and Cd were removed effectively via the addition of TMT and Fe3+ in the solution containing DTPA. Pb and Cd concentrations decreased from 50 mg/L to